STUDI REDUKSI BUNYI PADA MATERIAL INSULASI ATAP ZINCALUME - Kristanto, Luciana; Sugiharto, Handoko; Atmojo, Adrian Dwi; Loekito, Leonardus Budi Darmawan (DIMENSI (Journal of Architecture and Built Environment), 2012)
Sound Reduction Study of Insulator of Zinc-alume Metal-roofing. Metal roofing is a common upper-structure of wide-span building. The metal material usually used as roof covering is zinc-alume; which has better performance in strength, easy-construction and its durability than other metal material. Although it has good structural performance, its performance as a sound reduction to reduce noise to the room beneath still need to be studied further. Therefore this research aimed to study how zinc-alume and its insulator perform through air-borne noise, besides structure-borne/impact noise. Insulator has been studied here are the Orca-zinc coating, glasswool, rockwool and styrofoam. The measurement done in a reverberation chamber, with pink noise source in 125 Hz- 4000 Hz frequency.